2011
DOI: 10.1542/peds.2010-1867
|View full text |Cite
|
Sign up to set email alerts
|

Kingella kingae: An Emerging Pathogen in Young Children

Abstract: Kingella kingae is being recognized increasingly as a common etiology of pediatric osteoarticular infections, bacteremia, and endocarditis, which reflects improved culture methods and use of nucleic acid-amplification techniques in clinical microbiology laboratories. K kingae colonizes the posterior pharynx of young children and is transmitted from child to child through close personal contact. Day care attendance increases the risk for colonization and transmission, and clusters of K kingae infections among d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
193
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(198 citation statements)
references
References 58 publications
3
193
0
2
Order By: Relevance
“…After 36 mo, the carriage rate declined, probably due to the maturation of the children's immune system and/or an acquired humeral immunity to K. kingae carriage and invasive infection as a result of previous expositions (15)(16)(17)(18)(19). Our results show marked similarities to a recent study carried out by Amit et al (20) among a large cohort of healthy Israeli children; and previous data (13,16). A recent study by Amit et al (19) confirmed the age of 6-29 mo to be a significant risk factor for K. kingae colonization in two different ethnic groups of Israel.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…After 36 mo, the carriage rate declined, probably due to the maturation of the children's immune system and/or an acquired humeral immunity to K. kingae carriage and invasive infection as a result of previous expositions (15)(16)(17)(18)(19). Our results show marked similarities to a recent study carried out by Amit et al (20) among a large cohort of healthy Israeli children; and previous data (13,16). A recent study by Amit et al (19) confirmed the age of 6-29 mo to be a significant risk factor for K. kingae colonization in two different ethnic groups of Israel.…”
Section: Discussionsupporting
confidence: 88%
“…kingae has recently emerged as an important cause of OAI in young children (1)(2)(3)13). This organism belongs to the normal commensal flora of the posterior pharynx (14,15), but rarely penetrates the bloodstreams and invades distant organs (6,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly to S. pneumoniae, H. influenzae type b or Neisseria meningitidis, K. kingae resides in the mucosal surface and is able to penetrate the bloodstream, disseminate and invade distant organs. [9][10][11] Colonization of the respiratory tracts by these organisms is, therefore, a prerequisite for later invasion. For most of these microoorganisms, such as S. pneumoniae or H. influenzae, [2][3][4][5][6][7] there are evidences that the bacterial load varies in the nasopharynx with the age of subjects, and that higher nasopharynx colonization densities play major roles in the development of invasive infections.…”
Section: © 2013 Lippincott Williams and Wilkinsmentioning
confidence: 99%